A user-controlled thermal chair for an open plan workplace: CFD and field studies of thermal comfort performance - Shahzad, Sally; Calautit, John Kaiser; Aquino, Angelo I.; Nasir, Diana S.N.M.; Hughes, Ben Richard (Elsevier, 2017)
This study aims to improve user comfort and satisfaction regarding the thermal environment in the open plan office, which is a current challenge in the workplace addressed by limited research. The main difficulty in an open plan setting is that changing the room temperature in an area affects all occupants seated nearby. This issue in addition to individual differences in perceiving the thermal environment create a great challenge to satisfy all occupants in the workplace. This study investigates the application of an advanced thermal system, a user-controlled thermal chair, which allows individual control over their immediate thermal environment without affecting the thermal environment and comfort of other occupants. The performance of the chair was further analysed through Computational Fluid Dynamics (CFD) simulations providing a detailed analysis of the thermal distribution around a thermal chair with a sitting manikin. The results indicated that user thermal comfort can be enhanced by improving the local thermal comfort of the occupant. A prototype of an office chair equipped with thermal control over the seat and the back was produced and examined in an open plan office in November in Leeds, UK. Forty-five individuals used the chair in their everyday context of work and a survey questionnaire was applied to record their views of the thermal environment before and after using the chair. The results of the field study revealed 20% higher comfort and 35% higher satisfaction level, due to the use of thermal chair. Thermal measurements showed acceptable thermal conditions according to the ASHRAE Standard 55-2013. Over 86% of the occupants set the temperature settings of the seat and the back of the chair between 29 °C and 39°. 82% of the occupants expressed their satisfaction level as “satisfied” or “very satisfied” regarding the performance of the thermal chair. The thermal chair energy consumption was relatively low (0.03 kW) when compared with that of typical personal heaters, which are about 1–1.5 kW. Further research is recommended to improve the design and application of the thermal chair to improve user overall thermal comfort and also further reduce energy consumption.